Activity Pattern Analysis Indicates Increased but Balanced Systemic Coagulation Activity in Response to Surgical Trauma - Friedrich, Max Julian; Schmolders, Jan; Rommelspacher, Yorck; Strauss, Andreas; Rühl, Heiko; Mayer, Günter; Oldenburg, Johannes; Wirtz, Dieter Christian; Müller, Jens; Pötzsch, Bernd (TH Open, 2018)
In the nonbleeding patient, constant low-level activation of coagulation enables a quick procoagulant response upon an injury. Conversely, local activation of coagulation might influence the systemic activity level of coagulation. To characterize this interaction in more detail, activity pattern analysis was performed in patients undergoing elective surgeries. Blood samples were taken before, during, and 24 hours after surgery from 35 patients undergoing elective minor (n = 18) and major (n = 17) orthopaedic surgeries. Plasma levels of thrombin and activated protein C (APC) were measured using oligonucleotide-based enzyme capture assays, while those of prothrombin fragment 1.2, thrombin–antithrombin-complexes, and D-dimer were measured using commercially available enzyme-linked immunosorbent assays. In vitro thrombin generation kinetics were recorded using calibrated automated thrombography. Results showed that median plasma levels of up to 20 pM thrombin and of up to 12 pM APC were reached during surgery. D-dimer levels started to increase at the end of surgery and remained increased 24 hours after surgery, while all other parameters returned to baseline. Peak levels showed no significant differences between minor and major surgeries and were not influenced by the activity state at baseline. In vitro thrombin generation kinetics remained unchanged during surgery. In summary, simultaneous monitoring of the procoagulant and anticoagulant pathways of coagulation demonstrates that surgical trauma is associated with increased systemic activities of both pathways. Activity pattern analysis might be helpful to identify patients at an increased risk for thrombosis due to an imbalance between surgery-related thrombin formation and the subsequent anticoagulant response.
Keywords: coagulation; surgical hemostasis; DNA aptamers; biomarkers; enzyme activity